CFD modeling of ventilation ducts for improvement of air quality in closed mines. Issue 4 (3rd July 2016) - Park, Jongmyung; Park, Samgyu; Lee, Dong-Kil
Abstract: Decommissioned, dead-end mining tunnels or natural caves are employed to investigate new usage in Korea. Ventilation ducts are designed to allow control of flow velocities, mean age of air, and temperatures of blown air. Turbulent air flows within a dead-ended tunnel are theoretically predicted using the numerical code with a κ − ε turbulence model, and 3.5 M hexahedral grids. Three-dimensional turbulent transport, detailed flow structural characteristics, dimensionless temperature, and local mean age of air are considered to provide new insight into the mechanisms needed to design the ventilation duct for tunnels. Time-averaged turbulent flow characteristics, velocity shape path lines, fluid age distributions, and temperature distributions are presented for 5% inlet turbulence intensity and 12 m/s inlet velocity. From CASE1 to CASE6, six different geometries of ventilation duct are used to optimize the design for better air quality. Overall, the numerically predicted results show the air is fresher in the long duct and average temperatures in the tunnel with long ventilation ducts are slightly lower than those in a tunnel with short ducts.